Smaller sister - Willis, Maggie Edkins (Roaring Brook Press, 2022)
Lucy, a young girl has always looked up to her beloved big sister, Livy, but she has recently started to notice Livy's changes. Livy gets angrier and more withdrawn, until Lucy and the family find out Livy has an eating disorder. Apart from navigating middle school and making new friends, while dealing with bullies, now Lucy must find a way to help Livy heal and find her way back to being best friends and sisters.